Resistance, Extinction, and Everything in Between – The Diverse Responses of Seaweeds to Marine Heatwaves - Straub, Sandra C.; Wernberg, Thomas; Thomsen, Mads S.; Moore, Pippa J.; Burrows, Michael T.; Harvey, Ben P.; Smale, Dan A. (Frontiers in Marine Science, 2019)
Anomalously Globally, anomalously warm temperature events have increased by 34% in frequency and 17% in duration from 1925 to 2016 with potentially major impacts on coastal ecosystems. These ‘marine heatwaves’ (MHWs) have been linked to changes in primary productivity, community composition and biogeography of seaweeds, which often control ecosystem function and services. Here we review the literature on seaweed responses to MHWs, including 58 observations related to resistance, bleaching, changes in abundance, species invasions and local to regional extinctions. More records existed for canopy-forming kelps and bladed and filamentous turf-forming seaweeds than for canopy-forming fucoids, geniculate coralline turf and crustose coralline algae. Turf-forming seaweeds, especially invasive seaweeds, generally increased in abundance after a MHW, whereas native canopy-forming kelps and fucoids typically declined in abundance. We also found three four examples of regional extinctions of kelp and one example of fucoids extinction following specific MHWs, events that likely have long term consequences for ecological structure and functioning. Although a relatively small number of studies have described impacts of MHWs on seaweed, the broad range of documented responses highlights the necessity of better baseline information regarding seaweed distributions and performance, and the need to study specific characteristics of MHWs that affect the vulnerability and resilience of seaweeds to these increasingly important climatic perturbations. A major factor will be to disentangle impacts caused by the extreme temperature increases of MHWs itself from co-occurring potential stressors including altered current patterns, changes in water clarity and nutrient content, solar radiation and desiccation stress in the intertidal zone. With future increases anticipated in the intensity, duration and frequencies of MHWs, we expect to see more replacements of large long-lived habitat forming seaweeds with smaller ephemeral weeds, reducing the structure and effective services seaweed-dominated reefs can provide.